Religiosity, Locus of Control and Financial Behavior of Muhammadiyah Religious Administrators in North Maluku in Strengthening Organizations and Community Services - Abbas, Djamila; Fatah, Rahmat Abd; Soleman, Diah Aristantia; Marwa, Rila A. (Technium Social Sciences Journal, 2024)
This research aims to find the meaning of Religiosity, Locus of Control, and Financial Behavior of Muhammadiyah Administrators in North Maluku in Strengthening Organizations and Community Services. This research is very important to study because it is still rare to raise the topic. In addition, what distinguishes this research from the previous one lies in the sociological approach. While the qualitative method with the type of phenomenology is used to reveal meaning. The results found that religiosity serves as a foundation of values, as well as guiding decision-making and shaping the integrity of the board. High internal locus of control among the administrators indicates a belief in the ability to control the outcome of actions, in terms of financial behavior, it was found that the administrators showed discipline and prudence in the management of funds, In addition, this study reveals that collaboration with external parties is seen as a success factor in running social services. This research contributes to understanding how aspects of religiosity, locus of control, and financial behavior affect organizational strengthening and community service, and offers insights for the development of more effective strategies in religious and social contexts.